2017
DOI: 10.21608/jappmu.2017.45857
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Effects of Propolis on Preservation of Ram's Semen Extender and Its Fertility Rate

Abstract: The present study aimed to define the effect of different concentrations of propolis powder or glue extract compared with synthetic antibiotic on ram's semen quality, resistance to bacterial contamination and fertility rate. Semen samples of six mature rams aging 2.2 years old with an average 62.0 kg live body weight were collected twice a week for three weeks using artificial vagina. The semen ejaculates were pooled, extended and divided into seven portions. The final extension rate was 1 semen: 10 extender. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
3
4
0
Order By: Relevance
“…Also, there were significant (P < 0.01) increases in the spillage of alanine transaminase, aspartate transaminase, alkaline phosphatase and lactic dehydrogenase enzymes into the extracellular medium through preservation time. These finding are similar to those obtained by Mohamed (2017) and Mohamed et al (2019).…”
Section: Discussionsupporting
confidence: 93%
“…Also, there were significant (P < 0.01) increases in the spillage of alanine transaminase, aspartate transaminase, alkaline phosphatase and lactic dehydrogenase enzymes into the extracellular medium through preservation time. These finding are similar to those obtained by Mohamed (2017) and Mohamed et al (2019).…”
Section: Discussionsupporting
confidence: 93%
“…In harmony with our results, propolis extract in the extenders showed the highest ability to sustain the viability and motility of ram spermatozoa (Mohamed and Zanouny, 2017). Also, the percentage of live sperm with intact and detached acrosome was increased, while dead sperm with intact and detached acrosome was decreased by propolis addition in the extender of stored ram semen (Mohamed, 2017). Supplementation of semen extenders with 0.2% of propolis powder or glue increased sperm motility, livability, and normality of spermatozoa (Khalifa et al, 2016).…”
Section: Figuresupporting
confidence: 88%
“…In accordance these results, Akandi et al (2015) found that propolis supplementation with a semen extender improves sperm viability and DNA integrity. In addition, extenders containing propolis were reported to lower the release of enzymes such as ALT, AST, ALP, and LDH significantly into the sperm medium (Mohamed and Zanouny, 2017;Mohamed, 2017) which may reflect the high sperm membrane integrity during incubation and storage (Zeidan et al, 2004). Improving sperm characteristics in pre-freezing and post-thaw semen was explained by several authors.…”
Section: Figurementioning
confidence: 99%
“…Addition of propolis to semen ram extender (0.5 and 1.0 mg/mL; preserved at 5 °C for 48 h) enhanced sperm function, and antioxidant capacity as well as reduced the lipid peroxidation 13 . Moreover, several other studies shown a significant enhance in semen longevity in rabbits 14 , and ram 15 by propolis administration. Additionally, propolis was add to the cryopreserved semen media in fish 16 , goats 17 , bull 11 , ram 12 .…”
Section: Introductionmentioning
confidence: 81%